Agama dan Kekerasan terhadap Perempuan: Mencari Akar-Akar Kekerasan terhadap Perempuan Perspektif Islam - Sumbulah, Umi (el Harakah: Jurnal Budaya Islam, 2001)
Violence against women, especially domestic violence that is currently prevalent, is actually a multilevel and multi-dimensional problem. This paper explores the roots of violence against women at various social, educational and economic levels. In the literature of feminism, the frequent form of violence against women is also the exploitation and exploitation of women, belonging to the violence of pornography, the harassment of women's image and dignity. This paper also offers some thoughts to solve them, as follows: 1) Reinterpretation of sacred texts that are just and uphold the principles of equality between men and women; 2) Internalization and socialization of equality values in multi-level and social stratification of the community regardless of ethnicity, race, gender, religion and other social level; 3) Creation of a sakinah and harmonious household situation; 4) Continuity of movement and struggle against inequality and injustice against women, by men as well as by women themselves; 5) Handling of victims of violence, whether from psychological, legal, or other aspects; 6) Provision of legal facilities and political containers that accommodate the interests of women and counseling for the handling of violence. Kekerasan terhadap kaum perempuan khususnya kekerasan dalam rumah tangga yang saat ini marak terjadi, sebenarnya adalah masalah yang multilevel dan multi dimensional. Tulisan ini mengeksplorasi akar kekerasan terhadap kaum perempuan di berbagai tingkat sosial, pendidikan dan ekonomi. Dalam literatur-literatur feminisme, bentuk kekerasan terhadap perempuan yang sering juga dipersoalkan adalah eksploitasi dan seksploitasi terhadap perempuan, yang tergolong pada kekerasan pornografi, yakni pelecehan terhadap citra dan martabat perempuan. Tulisan ini juga menawarkan beberapa pemikiran untuk menyelesaikannya, sebagai berikut: 1) Reinterpretasi teks suci yang berkeadilan dan menjunjung tinggi prinsip-prinsip kesetaraan antara laki-laki dan perempuan; 2) Internalisasi dan sosialisasi nilai-nilai kesetaraan di multi level dan stratifikasi sosial masyarakat tanpa memandang etnis, ras, jenis kelamin, agama dan tingkat sosial lainnya; 3) Penciptaan situasi rumah tangga yang sakinah dan harmonis; 4) Kontinuitas gerakan dan perjuangan melawan ketimpangan dan ketidakadilan terhadap kaum perempuan, baik oleh laki-laki maupun perempuan sendiri; 5) Penanganan korban kekerasan, baik dari aspek psikis, hukum, maupun lainnya; 6) Penyediaan fasilitas hukum dan wadah politik yang mengakomodir kepentingan perempuan serta konseling untuk penanganan kekerasan.